In vivo genotoxicity of estragole in male F344 rats. (31st October 2014) - Ding, Wei; Levy, Dan D.; Bishop, Michelle E.; Pearce, Mason G.; Davis, Kelly J.; Jeffrey, Alan M.; Duan, Jian‐Dong; Williams, Gary M.; White, Gene A.; Lyn‐Cook, Lascelles E.; Manjanatha, Mugimane G.
Abstract : Estragole, a naturally occurring constituent of various herbs and spices, is a rodent liver carcinogen which requires bio‐activation. To further understand the mechanisms underlying its carcinogenicity, genotoxicity was assessed in F344 rats using the comet, micronucleus (MN), and DNA adduct assays together with histopathological analysis. Oxidative damage was measured using human 8‐oxoguanine‐DNA‐ N ‐glycosylase (hOGG1) and EndonucleaseIII (EndoIII)‐modified comet assays. Results with estragole were compared with the structurally related genotoxic carcinogen, safrole. Groups of seven‐week‐old male F344 rats received corn oil or corn oil containing 300, 600, or 1, 000 mg/kg bw estragole and 125, 250, or 450 mg/kg bw safrole by gavage at 0, 24, and 45 hr and terminated at 48 hr. Estragole‐induced dose‐dependent increases in DNA damage following EndoIII or hOGG1 digestion and without enzyme treatment in liver, the cancer target organ. No DNA damage was detected in stomach, the non‐target tissue for cancer. No elevation of MN was observed in reticulocytes sampled from peripheral blood. Comet assays, both without digestion or with either EndoIII or hOGG1 digestion, also detected DNA damage in the liver of safrole‐dosed rats. No DNA damage was detected in stomach, nor was MN elevated in peripheral blood following dosing with safrole suggesting that, as far both safrole and estragole, oxidative damage may contribute to genotoxicity. Taken together, these results implicate multiple mechanisms of estragole genotoxicity. DNA damage arises from chemical‐specific interaction and is also mediated by oxidative species. Environ. Mol. Mutagen. 56:356–365, 2015. © 2014 Crown copyright.